Sur un Exemple de Patrick Greussay - Danvy, Olivier (BRICS Report Series, 2004)
This note was written at the occasion of the retirement of Jean-Francois Perrot at the Universite Pierre et Marie Curie (Paris VI). In an attempt to emulate his academic spirit, we revisit an example proposed by Patrick Greussay in his doctoral thesis: how to verify in sublinear time whether a Calder mobile is well balanced. Rather than divining one solution or another, we derive a spectrum of solutions, starting from the original specification of the problem. We also prove their correctness.